Local government reforms and grassroots development in Nigeria / Ariyo Andrew Tobi and Gabriel Izokpu Oikhala - Tobi, Ariyo Andrew; Oikhala, Gabriel Izokpu (Universiti Teknologi MARA, 2021)
Local governments worldwide are concerned with the management of public affairs at the grassroots. In Nigeria, a series of reforms have been carried out on the local government system. Yet, the narrative shows that local governments have not been effective agents of grassroots governance and development. This study relied on data sourced from textbooks, journals, official publications and used a theory of localism to explain how the federal and state governments had incapacitated local governments. This paper argued that various reforms had attributed the perennial failure of the Nigerian local government system to the status of local government in the Nigerian federal arrangement. Nigerian Federal arrangement, particularly the relationship between local government and other government tiers, has continued to undermine the autonomy of the former to operate optimally. The study found that apart from poor implementation of recommendations of various committees, inconsistencies in the provisions of the constitutions, inadequate funding, and resistance by state governments have collectively undermined the effectiveness of local governments as the agents of grassroots governance and development in Nigeria. The study concluded that the effectiveness of Nigerian local governments would only improve considerably if the federal and state governments guarantee an atmosphere that would enable them to perform their statutory functions.